The identity and the life of the church : John Calvin's ecclesiology in the perspective of his anthropology - Kim, Yosep (Eugene, Oregon : Pickwick Publications, 2014)
The study of John Calvin's ecclesiology argues that Calvin's idea of the twofold identity of the Church--its spiritual identity as the body of Christ and its functional identity as the mother of believers--is closely related to his understanding of Christian identity and life, which are initiated and maintained by the grace of the triune God. The anthropological basis of Calvin's idea of the Church has not been examined fully, even though Calvin presents the important concepts of his ecclesiology in light of his anthropological ideas. This study offers an overall evaluation for Calvin's ecclesiology, arguing that it is ultimately his pastoral concern for the Christian and the Church under affliction that both governs his theological understanding of the Church and shapes his proposals for establishing and sustaining the life of the Church in the world.--Back cover.
Includes bibliographical references and index.
Print version record.
Keywords: Calvin, Jean, -- 1509-1564.; Calvin, Jean, -- 1509-1564 -- Anthropology; Calvin, Jean, -- 1509-1564 -- Contributions in the doctrine of the church; Church -- History of doctrines -- 16th century; RELIGION / Christian Theology / Ecclesiology; Electronic books